2018
DOI: 10.3389/fmars.2018.00204
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Nutrient Resorption and Export Fluxes of Avicennia marina in the Central Red Sea Area

Abstract: Red Sea mangroves occur in an oligotrophic sea without permanent freshwater inputs. Understanding the mechanisms to cope with nutrient limitation is, therefore, important to understand their distribution and nutrient dynamics in coastal ecosystems. We measured total number of meristems to estimate their leaves production and nutrients (N, P, and Fe) as a function of age in Avicennia marina leaves. Then estimated resorption rates; the recovery of nutrients from senescing leaves before they are shed in a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
1
15
2
Order By: Relevance
“…The Red Sea is a semi-enclosed highly oligotrophic basin (Acker et al, 2008;Raitsos et al, 2013). It is known as one of the warmest tropical seas, with maximum sea surface temperatures ranging from 33.0 to 33.9 • C during summer (Chaidez et al, 2017;Osman et al, 2018), and up to 34-35 • C in certain parts of the basin (Rasul et al, 2015;Garcias-Bonet and Duarte, 2017;Almahasheer et al, 2018). Due to the prevailing arid conditions, the Red Sea experiences large evaporation rates (nearly 2 cm yr −1 of freshwater from the surface layers) while the lack of river runoff and low precipitation rates make this system one of the saltiest seas on the planet (Sofianos, 2002;Sofianos and Johns, 2015;Zarokanellos et al, 2017).…”
Section: C López-sandoval Et Al: Rates and Drivers Of Red Sea Plmentioning
confidence: 99%
See 1 more Smart Citation
“…The Red Sea is a semi-enclosed highly oligotrophic basin (Acker et al, 2008;Raitsos et al, 2013). It is known as one of the warmest tropical seas, with maximum sea surface temperatures ranging from 33.0 to 33.9 • C during summer (Chaidez et al, 2017;Osman et al, 2018), and up to 34-35 • C in certain parts of the basin (Rasul et al, 2015;Garcias-Bonet and Duarte, 2017;Almahasheer et al, 2018). Due to the prevailing arid conditions, the Red Sea experiences large evaporation rates (nearly 2 cm yr −1 of freshwater from the surface layers) while the lack of river runoff and low precipitation rates make this system one of the saltiest seas on the planet (Sofianos, 2002;Sofianos and Johns, 2015;Zarokanellos et al, 2017).…”
Section: C López-sandoval Et Al: Rates and Drivers Of Red Sea Plmentioning
confidence: 99%
“…In tropical and subtropical oligotrophic regions, the high temperatures may amplify the metabolic imbalances in plankton communities as CR tends to increase faster than GPP (Harris et al, 2006;Regaudie-de-Gioux and Duarte, 2012) if the allochthonous sources of organic carbon are enough to subsidise their carbon demand. These allochthonous inputs may be delivered from land through riverine discharge, from the atmosphere through atmospheric deposition of dust and volatile organic carbon (Jurado et al, 2008), or are exported from productive coastal habitats (Duarte et al, 2013; Barrón and Duarte, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although this will lead to a reduction of heavy metals in soils, shedding of e.g., mangrove leaves could transfer metals from deep soil layers into the soil surface and elsewhere in the ecosystem, so that rather than sequestering metals mangroves could be remobilizing pollutants within the ecosystem. Despite pollution in mangroves have been widely studied Zhang et al, 2014;Alzahrani et al, 2018;Kulkarni et al, 2018), and previous studies showed that mangroves have the capacity to reabsorb nutrients before shedding the leaves (Alongi et al, 2005;Zhou et al, 2010;Almahasheer et al, 2018), the fate of metals remains largely unknown (Saenger and McConchie, 2004). Therefore, the elemental fluxes between bio-and geospheres of mangrove ecosystems and in particular, the dynamics of heavy metals in mangrove leaves remain, to the best of our knowledge, unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we examined the capacity of Avicennia marina in the Red Sea to reabsorb N, P, and Fe prior to leave senescence, and despite evidence of Fe deficiency, mangroves had low resorption of Fe (42%) compared to N and P (69 and 72%, respectively; (Almahasheer et al, 2018). Whether these applies to other heavy metals or not is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In tropical and subtropical oligotrophic regions, the high temperatures may amplify the metabolic imbalances in plankton communities as CR tends to increase faster than GPP Regaudie-de-Gioux and Duarte, 2012) if the allochthonous sources of organic carbon are enough to subsidise their carbon demand. These allochthonous inputs may be delivered from land through riverine discharge, from the atmosphere through atmospheric deposition of dust and volatile organic carbon (Jurado et al, 2008), or are exported from productive coastal habitats Barrón and Duarte, 2015). The Red Sea is a semi-enclosed highly oligotrophic basin (Acker et al, 2008;Raitsos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%